Matoša problematyzacje piękna. Tropem pewnego poszukiwania - Czapik-Lityńska, Barbara (Wydawnictwo Nauka i Innowacje, 2014)
The article describes the transformations of the traditional category of beauty in the Croatian modernist discourse. Based on the analysis of works of Matoš, we offer a study of modernist concepts of beauty, manifested in the relations between beauty, art and life. The discourse in question simultaneously transforms and explains the sense of beauty, introduces into the world of aesthetic and artistic values central to the culture of modernism.
Matoš’s Beauty Problematizations. Following Some Research
Keywords: modernism; aesthetic categories; literary construction; style; artistry; the sense of beauty; artistic value; aesthetic value